2011
DOI: 10.1097/rlu.0b013e31822f684b
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of FDG PET Imaging in Predicting Metastatic Potential and Assessment of Therapeutic Response to Neoadjuvant Chemotherapy in Ewing Sarcoma Family of Tumors

Abstract: FDG uptake in primary ESFT reflected its metastatic potential and hence the aggressive behavior. The significant correlation between change in metabolic activity of the primary tumor and histopathological response after neoadjuvant chemotherapy suggests that FDG PET may be an ideal noninvasive method to assess tumor behavior and response to therapy in ESFT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 22 publications
0
18
1
2
Order By: Relevance
“…Functional imaging such as positron emission tomography (PET) was studied with more promising results. In a series of 36 patients, absolute value of standard uptake value (SUV) of PET tracer after neoadjuvant chemotherapy was predictive of PFS[21], and a study of 14 patients demonstrated a correlation between the relative change in SUV and histologic response[22]. In our study, there was no correlation between radiologic response and histologic response, but different radiologic measures were associated with disease outcomes.…”
Section: Discussionmentioning
confidence: 50%
“…Functional imaging such as positron emission tomography (PET) was studied with more promising results. In a series of 36 patients, absolute value of standard uptake value (SUV) of PET tracer after neoadjuvant chemotherapy was predictive of PFS[21], and a study of 14 patients demonstrated a correlation between the relative change in SUV and histologic response[22]. In our study, there was no correlation between radiologic response and histologic response, but different radiologic measures were associated with disease outcomes.…”
Section: Discussionmentioning
confidence: 50%
“…FDG uptake has also been correlated with the expression of HIF-1α [9] and was found significantly increased in the primary Ewing sarcoma family of tumors with distant metastasis [10]. On the other hand, it has been also reported that it remains challenging for 18 F-FDG PET to reliably differentiate chronically hypoxic from normoxic tumors [11] or malignant lesions from benign inflammatory processes [12].…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic information from 18 F-FDG-PET scans may improve therapy response assessment, especially for tumors with small extraosseous soft tissue components [87, 88]. Due to its high soft tissue contrast, 18 F-FDG PET/MR can accurately diagnose hypermetabolic brown fat and hypermetabolic reconverted hematopoietic marrow after chemotherapy [8991].…”
Section: Improve the Accuracy For The Diagnosis Of Treatment Responsementioning
confidence: 99%